Promoting condom negotiation self-efficacy among young women in China: the effects of traditional sexual values and descriptive norms. - Zhang, Lin; Mou, Yi; Zhang, Lianshan (Health Education Research, 2023)
This study attempts to design effective messages to promote condom negotiation self-efficacy and safer sex intent among young women in China. An online experiment with 2 (descriptive norm: present versus absent) × 2 (traditional sexual value: high versus low) between-subjects factorial design was conducted on a purposive sample of 241 female Chinese college students. The results demonstrated that culturally tailored messages incorporating descriptive norms information on the popularity of condom negotiation can increase participants' self-efficacy (F (1,237) = 9.01, partial η2  = 0.04, P  = 0.003) but not safer sex intent (F (1,237) = 2.80, partial η2  = 0.01, P  = 0.096). Participants with a lower level of traditional sexual values had similar levels of condom negotiation self-efficacy as those with a higher level of values: F (1,237) = 2.85, partial η2  = 0.01, P  = 0.09. There were no significant interaction effects of traditional sexual value and descriptive norm on condom negotiation self-efficacy and safer sex intent. The findings contribute to the cultural sensitivity perspective in health education in an Eastern context and have implications for public health practitioners and policymakers.